Re-Design Alat Tanam Bawang Merah di Kecamatan Sukomoro Kabupaten Nganjuk - Nugroho, Risky Alifian; Hendrawan, Aloysius Tommy; Susanto, Doni (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to redesign an ergonomic red onion planting tool to improve work efficiency for farmers in Sukomoro District, Nganjuk Regency. The main problems faced by farmers include uncomfortable working posture, long planting times, and high dependence on manual labor. By applying ergonomic principles and using local anthropometric data, a new tool was designed and tested directly by 20 farmer respondents. The results showed that the redesigned tool reduced average planting time by up to 20% compared to the previous tool and received positive responses from the majority of farmers based on a satisfaction questionnaire. The tool was developed with consideration for user comfort, planting distance accuracy, and ease of operation. This study concludes that the redesigned planting tool is feasible to be used as an effective and sustainable mechanization solution to enhance productivity and farmer welfare in red onion cultivation.